Improving the Role of Financial and Business Activity of Enterprises - Akhmedova A. T. (International Journal on Integrated Education, 2021)
The article is devoted to the study and characterization of the problems of financial and business activity of enterprises, as well as the search for measures related to improving the efficiency of resource use.